2020
DOI: 10.4103/jehp.jehp_139_20
|View full text |Cite
|
Sign up to set email alerts
|

Disciplinary-based information literacy skills among medical students

Abstract: INTRODUCTION: Disciplinary-based information literacy (DIL) or professional-related information literacy has not been widely studied in the academic context, including medical sciences. This study aimed at investigating the status of DIL among medical students in an Iranian medical university. MATERIALS AND METHODS: This study was a cross-sectional survey. A random sample consisting of 298 students majoring in general medicine at Tehran University of Medical Science, Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…These results were anticipated as the information literacy instruction programs in the medical libraries of Pakistan were in the infancy stage as most of the medical libraries used library orientations, bibliographic instructions, and occasional lectures as a method of information literacy delivery [ 54 , 55 ]. These results were in line with that of Ganesan and Gunasekaran [ 56 ] and Panahi et al [ 4 ] who also reported that the information literacy skills of medical students were at a minimal level than expected. These findings were also supported by Ullah and Ameen [ 57 ] reporting that the Pakistani medical librarians also perceived the information literacy skills of medical students as inadequate.…”
Section: Discussionsupporting
confidence: 92%
“…These results were anticipated as the information literacy instruction programs in the medical libraries of Pakistan were in the infancy stage as most of the medical libraries used library orientations, bibliographic instructions, and occasional lectures as a method of information literacy delivery [ 54 , 55 ]. These results were in line with that of Ganesan and Gunasekaran [ 56 ] and Panahi et al [ 4 ] who also reported that the information literacy skills of medical students were at a minimal level than expected. These findings were also supported by Ullah and Ameen [ 57 ] reporting that the Pakistani medical librarians also perceived the information literacy skills of medical students as inadequate.…”
Section: Discussionsupporting
confidence: 92%